Relationship between TIM-3 gene polymorphisms and steroid-resistant primary nephrotic syndrome in children - Lei, Jing; Ma, Songdong (Cellular and Molecular Biology, 2020)
Nephrotic syndrome, also known as nephrosis, is a collection of symptoms in medicine and urology caused by damage to the basement membrane of the kidney glomeruli and the kidneys excrete a large amount of protein. This experiment was carried out to investigate the association of three single nucleotide polymorphisms (SNPs) of T-cell immunoglobulin and mucin-domain-containing-3 (Tim-3) with childhood primary nephrotic syndrome (PNS) steroid response in Han Chinese. For this purpose, a total of 218 children with steroid-resistant PNS and 189 children with steroid-responsive PNS were enrolled in this case-control study. Three single nucleotide polymorphisms (SNPs) of the TIM-3 gene promoter region (rs4704853, rs1051746, and rs10053538) were analyzed by polymerase chain reaction (PCR) and restriction enzyme digestion. Results showed that there were 124 males and 94 females in the steroid-resistant PNS group and 114 males and 75 females in the steroid-responsive PNS group. The mean ages of the two groups were 7.9 years and 7.7 years, respectively. The distribution of alleles of Rs1051746 and Rs10053538 were significantly different between the steroid-resistant PNS group and the steroid-responsive PNS group (P-value = 0.047 and 0.012, respectively). The distribution of their genotypes was also significantly different between the steroid-resistant PNS group and the steroid-responsive PNS group (P-value = 0.044 and 0.010, respectively). Haplotype G-C-G was less frequent among steroid-resistant PNS children than the steroid-responsive PNS children (P = 0.015). There was no significant difference between the three SNPs of TIM-3 and the clinical features of these PNS children (P>0.05). It concluded that this study provided evidence showing that the polymorphisms of Rs1051746 and Rs10053538 at the TIM-3 gene were related to childhood PNS steroid response. This result provided fundamental support for future studies on the role of TIM-3 in pathogenesis and therapy of childhood PNS.